2021
DOI: 10.3389/fimmu.2021.802085
|View full text |Cite
|
Sign up to set email alerts
|

Roles of LncRNAs in Regulating Mitochondrial Dysfunction in Septic Cardiomyopathy

Abstract: Sepsis is an abnormal systemic inflammatory response of the host immune system to infection and can lead to fatal multiorgan dysfunction syndrome. Epidemiological studies have shown that approximately 10-70% of sepsis cases can lead to septic cardiomyopathy. Since the pathogenesis of septic cardiomyopathy is not clear, it is difficult for medical doctors to treat the disease. Therefore, finding effective interventions to prevent and reduce myocardial damage in septic cardiomyopathy is clinically significant. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…Recent studies have found that once sepsis is combined with myocardial damage, it can aggravate the evolution of the disease, increase the risk of multiple organ failure and death, and seriously affect the prognosis of the patient. It was shown that about 40% to 50% of sepsis patients have cardiac insufficiency, and sepsis-induced myocardial dysfunction (SIMD) is an increasingly recognized form of transient cardiac dysfunction characterized by decreased ventricular systolic and diastolic function, and/or reduced response to volume resuscitation ( Zhang et al., 2020 ; Liu and Chong, 2021 ). A historical cohort study of 388 patients hospitalized with severe sepsis or septic shock demonstrated that even isolated right ventricular dysfunction is associated with worse long-term survival ( Vallabhajosyula et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that once sepsis is combined with myocardial damage, it can aggravate the evolution of the disease, increase the risk of multiple organ failure and death, and seriously affect the prognosis of the patient. It was shown that about 40% to 50% of sepsis patients have cardiac insufficiency, and sepsis-induced myocardial dysfunction (SIMD) is an increasingly recognized form of transient cardiac dysfunction characterized by decreased ventricular systolic and diastolic function, and/or reduced response to volume resuscitation ( Zhang et al., 2020 ; Liu and Chong, 2021 ). A historical cohort study of 388 patients hospitalized with severe sepsis or septic shock demonstrated that even isolated right ventricular dysfunction is associated with worse long-term survival ( Vallabhajosyula et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Septic cardiomyopathy, also known as sepsis-induced myocardial dysfunction, was rst described in 1984 as a reversible myocardial depression with an initial decrease in left ventricular ejection fraction accompanied by a decrease in cardiac index [6] . However, with the continuous updating of relevant studies, we found that not only left ventricular systolic dysfunction exists in septic cardiomyopathy, but also left ventricular diastolic dysfunction and right ventricular systolic dysfunction [7] . Although septic cardiomyopathy has not been clearly de ned, most scholars agree that septic cardiomyopathy is a reversible myocardial depression characterized by left ventricular dilatation and biventricular systolic and/or diastolic dysfunction, and the recovery period is 7-10 days [8] .…”
Section: Introductionmentioning
confidence: 91%
“…Sj-Cys could alleviate excessive inflammation and protect against sepsis-induced cardiac dysfunction in a mouse model of sepsis-induced myocardial injury. [10] Similarly, melatonin has been investigated as a potential treatment, [18,37,38] as evidenced in a study where a mouse model showed that melatonin is effective in attenuating septic myocardial injury. [38] Furthermore, gene therapy is promising as a possible therapeutic agent for septic cardiomyopathy and may reduce the inflammation associated with sepsis, improving cardiac function.…”
Section: Potential Treatment Optionsmentioning
confidence: 99%